Knowledge about hypertension and associated factors among patients with hypertension in public health facilities of Gondar city, Northwest Ethiopia: Ordinal logistic regression analysis. - Maereg Wolde; Telake Azale; Getu Debalkie Demissie; Banchilay Addis (PLoS ONE, 2022)
Background Hypertension is a disease that imposes risks of diseases on multi-system. Failure to control hypertension leads patients to end up with unavoidable complications, including death. Noncompliance to treatment is the main factor to develop such devastating complications whereas knowledge of patients about their disease is a key factor for better compliance. Thus, the purpose of this study is to assess the level of knowledge about hypertension and associated factors among hypertensive patients in public health facilities of Gondar city. Methods Facility-based cross-sectional study was conducted between March and April 2019 in Gondar town. A systematic sampling technique was applied to select a total of 389 patients. A structured interview questionnaire was used to gather the data. The data were analyzed using STATA version 14. Ordinal logistic regression analysis was performed at P < 0.05 with a 95% confidence interval to identify statistically significant variables. Results A total of 385 respondents participated giving a response rate of 98.9%. The majority (55.3%) of the patients had a low level of, 17.9% had a moderate level of knowledge whereas 26.8% had a high level of knowledge about hypertension. Those working in government organizations had 5.5 times higher odds of having a high level of knowledge than other groups (AOR = 5.5; 95%CI = 1.21, 25). Patients who received longer than four years of treatment showed twice larger odds of knowledge than those with below two years of treatment (AOR = 2; 95%CI = 1.29, 3.22) Moreover, patients residing proximate to the hospital increases the odds of having a higher level of knowledge by 1.64 times versus patients living far away from the hospital (AOR = 1.64, 95% CI = 1.07-2.63). Conclusions This finding revealed that knowledge about hypertension and risk factors among patients with hypertension was low. Employment in governmental organizations, longer duration of treatment, and residential proximity to hospitals/ health centers were statistically significant predictors of the participants' knowledge about hypertension. Therefore, it is important to give health education to patients working in non-governmental organizations and self-employed individuals about diseases and risk factors. In addition, emphasis should be given to patients receiving less than two years of treatment and coming from remote areas to improve their knowledge of the disease.